Case series of retroperitoneal cyst: a clinical challenge and diagnostic dilemma - Puvvada, Prashanth; Kalyanashanmugam, Sivakumar; Chidambaranathan, Sugumar (International Surgery Journal, 2024)
Cyst in retroperitoneal region is a rare occurrence with reported incidence of 1 in 5750-2,50,000. They present incidentally in one third patients or with pain or sometimes clinical palpable painless mass. Their management remains a clinical dilemma. Here, we report five cases of retroperitoneal cyst which presented to our hospital between August 2022-February 2023 and summarize the clinical features, diagnosis, and their treatment. All patients presented to our outpatient department. All patients were female youngest 20 years and oldest 76 years of age. Two patients had pain abdomen with clinically palpable mass. Two patients had painless mass. One patient was detected incidentally. All the patients were evaluated with CECT and MRI pelvis wherever needed. Cyst excision was done laparoscopically in 3 patients and by open laparotomy in 2 patients and histopathology report was followed post operatively. All patients were discharged without any complications. Retroperitoneal cyst is uncommon pathology of abdomen. Their presentation is quite vague. Imaging is the key in diagnosis. It poses a great clinical challenge in the management of such patients due to suspected malignancy. Our study shows that these cysts can be managed with simple excision irrespective of size after evaluation and laparoscopic approach is better where feasible.